Effect of living high and training low on sea level performance in cyclists - Mattila, V.; Rusko, H. (Medicine & Science in Sports & Exercise, 1996)
Five male competitive cyclists trained at sea-level and lived 18 hours daily for 11 days in a normobaric hypoxic environment (14.2% O2 -- 3,000 m equivalent). Sea-level time trials were performed five days before and after the acclimatization period. Performance, erythropoietin, and reticulocyte counts increased after the "simulated altitude" adaptation. No control group was used and so findings could be confounded. Some other variable might explain the changes recorded. This study is typical of much altitude research which fails to provide adequate controls to allow accurate attributions to observed changes. Thus, this report does not qualify as an acceptable piece of research. Implication: This no-control-group study can only suggest hypothetical relationships. True, controlled experimentation needs to be conducted to answer the questions which are raised.